The influence of post-operative knee coronal alignment parameters on long-term patient-reported outcomes after closed-wedge high tibial osteotomy - Goto, Norio (J Orthop, 2020)
BACKGROUND: Both intra-articular and extra-articular knee alignment pathologies can affect clinical outcomes after high tibial osteotomy. The purpose of this study was to investigate post-operative knee coronal alignment parameters that affect long-term patient-reported outcomes after closed-wedge high tibial osteotomy (CW-HTO). METHODS: This study included 105 osteoarthritic knees that underwent CW-HTO. Long-term patient-reported outcomes were defined by the 2011 Knee Society Score (KSS) and were collected at an average follow-up of 10.2 years. Post-operative knee coronal alignment parameters, consisting of the femoral tibial angle (FTA), lateral distal femoral angle (LDFA), medial proximal tibial angle (MPTA), tibial plateau inclination (TPI), and joint line convergence angle (JLCA), were measured using standing radiographs of the knee at an average follow-up of 11.0 months. The correlations between these parameters and KSS were then assessed by Spearman's correlation analysis. Comparisons of groups classified by MPTA and TPI cutoff values were performed by the Wilcoxon rank-sum test. RESULTS: Post-operative JLCA showed a significant negative correlation with two KSS sub-scores: satisfaction (R = −0.2232, P = 0.022) and total function (R = −0.2059, P = 0.035). There was no significant difference in any KSS sub-score between the “low” groups (MPTA and TPI less than 95 and 5°, respectively) and the “high” groups (MPTA and TPI greater than 98 and 7°, respectively). CONCLUSIONS: Among knee coronal alignment parameters, a large post-operative residual JLCA, which is an intra-articular varus deformity, was independently associated with worsened long-term clinical outcomes after CW-HTO. LEVEL OF EVIDENCE: Level Ⅳ, Retrospective cohort study.